Sustainable waste management assessment for Kota Lama Semarang heritage area - Milasari Titik Dinna; Purwanto; Luqman Yanuar (E3S Web of Conferences)
The implementation of waste management is a recurring challenge in Indonesia, particularly in tourist areas. In practice, there is a positive correlation between the increase in waste volume and tourism activities. Kota Lama Semarang, a heritage tourism site, serves as a hub for trade and tourism, attracting numerous domestic and international visitors has led to a rise in waste volume posing risks to urban resilience. Furthermore, sustainable waste management can contribute to reducing greenhouse gas emissions and support climate resilience. This study examines the implementation of sustainable waste management in the Heritage Area of Kota Lama Semarang using a quantitative approach. Data collection methods such as questionnaires, field observations, interviews, and document review. The collected data were then analyzed descriptively to evaluate the implementation of sustainable waste management in Kota Lama Semarang. The results indicate that waste management practices in the Kota Lama area have achieved a degree of sustainability, particularly concerning physical and non-physical components. As a result, waste management in the Kota Lama area remains under control. Additionally, it is crucial to foster collaboration among stakeholders and implement waste sorting practices such Waste Bank to promoting a circular economy in waste management.